A STUDY ON LIFE MANAGEMENT OF CHILDREN AND ADOLESCENTS IN THE JUVENTICE JUSTICE PROCESS WITHIN THE CONTEXT OF PRISONS AND DETENTION CENTERS IN PHRA NAKORN SI AYUTTHAYA PROVINCE - Thatsananchalee, Piyawan; Bhutasang, Natchana; Silavanich, Praepim; Senkas, Aranda; Nancha, Kridsada (Journal of Social Science and Cultural, 2023)
This case study of qualitative research aims to 1) study the conditions that affect life and 2) study any process that was used to manage the life crisis of a person who was the first to enter prison. This research methodology used a case study method by in-depth interviews to collect the data. Include criteria choosing children and youth who entered prison the first time and had been trying to hurt/ suicide themselves, so this group was special close surveillance, but they can manage their problem by themselves. The data was collected after the prison’s officials allowed suggestions and analyze by content analysis. All 12 key informants were allowed to reflect management of life crises to the researcher for 1-2 hours. The results showed that the top 3 factors of life crisis are 1) family factors, 2) Educational factors, and 3) Living environment factors. However, the crisis management process consists of 4 directions: 1) Problem coping, we found that problem coping was the process of activating something problem by separating the problem into groups and solving each problem by sort. 2) Divert attention from the problem to another activity. These results found the times that affected increased negative situations were resting time and time for family visiting time because the prisoner would focus on this golden time. The variety of activities can support the prisoner to decrease negative time. 3) Think about their values and use their abilities to benefit others. 4) Positive relationships, almost all the informants were fearful when they entered the prison for the first time, but they felt better because of their friend. After they had friends who had experience in managing life crises so informant will get suggestion for survival and resilience.